Nephroprotective Effects of Benzyl Isothiocyanate and Resveratrol Against Cisplatin-Induced Oxidative Stress and Inflammation - Ibrahim, Abdelazim; Al-Hizab, Fahad A.; Abushouk, Abdelrahman Ibrahim; Abdel-Daim, Mohamed M. (Frontiers in Pharmacology, 2018)
This study was performed to compare the nephroprotective effects of benzyl isothiocyanate (BITC) and resveratrol (RES) and investigate the nephroprotective efficacy of their combination against cisplatin-induced acute renal injury. Five animal groups (each of eight) received either normal saline, a single intraperitoneal injection of cisplatin (5 mg/kg) at the sixth day, cisplatin plus oral RES (30 mg/kg) or BITC (100 mg/kg in diet) or a combination of both for 10 days. Compared to saline-treated mice, cisplatin-intoxicated mice had significantly higher (p<0.05) serum levels of urea, creatinine, interleukin-1 (IL-1) and tumor necrosis factor-α. Moreover, biochemical analysis of kidney tissue homogenates showed that cisplatin intoxication was associated with significantly higher (p<0.05) tissue levels of malondialdehyde (MDA) and lower levels of reduced glutathione and activities of endogenous antioxidant enzymes (glutathione peroxidase, superoxide dismutase and catalase) in comparison to normal controls. Histopathological and immunohistochemical examinations of renal tissue slices from cisplatin-intoxicated mice showed interstitial leukocytic infiltration, tortuous tubules with vacuolated epithelium, luminal casts and overexpression of cyclooxygenase-II enzyme. On the other hand, treatment with RES or BITC ameliorated all the previous parameters. The effects of both compounds were comparable in all assessed parameters, except IL-1 serum concentration and renal tissue MDA concentration (which were significantly lower in RES group). Interestingly, treatment by BITC and RES combination restored the normal concentrations of all the aforementioned biochemical parameters, as well as near normal histological and immunohistochemical pictures. In conclusion, BITC exerted nearly comparable nephroprotective, antioxidant, and anti-inflammatory effects to RES and the combination of both agents showed more potent nephroprotective effects against cisplatin than each one alone.